Does Gamification Play a Role in Enhancing English Learning for Young Learners? - Hanim, Lathifah; Wahyuningsih, Sri (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
Proficiency in English is a fundamental prerequisite for accessing significant information within the international context. The present study aims to explore teachers’ and students’ experiences and views on the role of gamification in English learning. Utilizing a qualitative case study method, the data were collected from questionnaires distributed to five English teachers using gamification and twenty-one young learners who have participated in English learning using gamification through Google Forms. The results showed that gamification has a crucial role to play in improving the quality of young learners in English learning, which is adjusted to the implementation of gamification into English learning with effective game strategies used. The use of gamification can benefit students by engaging them and stimulating their creativity in learning English. In addition, teachers used strategies in using gamification during the English learning process including using picture guessing games, broken phone games, English crossword games, answering questions, guessing English words and Indonesian games while singing, Simon Says games, and rolling word games to digital games like cooking games, puzzle games, Pou games, and other enjoyable games. At last, the policy recommendation is outlined in this article based on the research findings.